2018
DOI: 10.1111/crj.12763
|View full text |Cite
|
Sign up to set email alerts
|

Static hyperinflation is associated with ventilatory limitation and exercise tolerance in adult cystic fibrosis

Abstract: Clinicians working with this patient group in a pulmonary rehabilitation or health care setting may wish to consider using measures of static hyperinflation as end points to determine program or treatment efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In COPD patients, EFL T promotes dynamic hyperinflation, with a concomitant increase in inspiratory work of breathing, impairment of inspiratory muscles function and adverse effects on hemodynamics. Also in CF patients ELF T is associated with lung hyperinflation, which in turn limits exercise . Moreover, in a recent longitudinal study conducted in adult CF patients, Vilozni, and colleagues found that the onset of EFL T predicts a decline in clinical course better than FEV1 and other spirometric indices …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In COPD patients, EFL T promotes dynamic hyperinflation, with a concomitant increase in inspiratory work of breathing, impairment of inspiratory muscles function and adverse effects on hemodynamics. Also in CF patients ELF T is associated with lung hyperinflation, which in turn limits exercise . Moreover, in a recent longitudinal study conducted in adult CF patients, Vilozni, and colleagues found that the onset of EFL T predicts a decline in clinical course better than FEV1 and other spirometric indices …”
Section: Discussionmentioning
confidence: 99%
“…8,28,29 33 which in turn limits exercise. [33][34][35][36] Moreover, in a recent longitudinal study conducted in adult CF patients, Vilozni, and colleagues found that the onset of EFL T predicts a decline in clinical course better than FEV1 and other spirometric indices. 13 In conclusion, in the present study the within-breath analysis of respiratory system impedance provided interesting insights in the physiological changes associated with early CF lung disease, suggesting the occurrence of dynamic airway compression, which may eventually lead to EFL T .…”
Section: Similarly the Poor Association Between Within-breath Fot Pamentioning
confidence: 99%
“…Thus, ventilation inhomogeneity is correlated with exercise limitation. In another study in 107 adult patients with CF, lung static hyperinflation, defined as RV/TLC > 0.30, was associated with a significant reduction in VO2 peak . Multilinear regression showed that the contribution of static inflation to exercise performance was greater than that of airway obstruction, measured by FEV1.…”
Section: Physiological Assessmentmentioning
confidence: 94%
“…In another study in 107 adult patients with CF, lung static hyperinflation, defined as RV/TLC > 0.30, was associated with a significant reduction in VO2 peak. 97 Multilinear regression showed that the contribution of static inflation to exercise performance was greater than that of airway obstruction, measured by FEV1. Evaluation of optimal markers of disease severity beyond traditional CPET outcomes, are also being investigated.…”
Section: Cardiopulmonary Exercise Testingmentioning
confidence: 99%
“…Aerobic exercise remains an integral part of the management of people with CF, and is associated with a reduction of the rate of decline in lung function and improved quality of life and bone mineralisation [3][4][5][6][7] . However, disease progression and the associated structural damage results in increased airway resistance, static and dynamic hyperinflation, hypoventilation and ventilationperfusion mismatch, all of which reduce exercise tolerance [8][9][10][11] . Patients can present with dyspnoea and fatigue during exercise, with exercise-induced hypoxaemia or desaturation occurring in 15 to 30% of cases [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%